SUSTAINABLE MIDWIFERY CARE IN Mrs. “P” FROM PREGNANCY UNTIL THE POSTPARTUM PERIOD AT POLINDES SUKOREJO BOJONEGORO 2019 - Nur Azizah; Sri Luluk; Wiwik Muhidayati; Rike Ariani (International Journal of Midwifery Research, 2022)
Pregnancy with a distance of children <2 years is the distance between one pregnancy and the next less than 2 years. Pregnancy with a distance of children <2 years is one of the complications / causes of high cases of maternal and infant mortality. Pregnancy and childbirth require professional services  by skilled health personnel. Solving maternal health problems needs to use an ongoing health care approach from before pregnancy, pregnancy, childbirth, childbirth, and contraception. This Final Project Report method uses varney management by documenting SOAP. The subjects of this study were third trimester pregnant women, labor, postpartum, contraception, and newborns (BBL). Data collection was carried out with history, physical examination, investigation, analyzed according to midwifery care diagnosis. The results of the study showed that the care given ended with physiological results. Care is given focus on trimester III pregnancy, care provided with a standard 10 T, delivery with 60 steps APN, childbirth with 4 visits, BBL with 3 visits, and midwifery care for postpartum contraception services with the results of mothers using postpartum contraception. There was no gaps in the application of midwifery care between the theory and practice of midwifery care that is on the ground, and must be maintained to improve the degree of maternal and child health services and be able to detect early complications that can reduce high maternal and infant mortality and morbidity.